The effect of interface stress on the grain boundary grooving in nanomaterials: Application to the thermal degradation of Cu/W nano-multilayers. (1st July 2021) - Druzhinin, A.V.; Cancellieri, C.; Jeurgens, L.P.H.; Straumal, B.B.
Abstract: The phenomenon of non-equilibrium grain boundaries and interphase boundaries is very important for materials science. They can be found in materials after sever plastic deformation, rapid quenching etc. In the present work, the influence of interface stresses on the energy of Cu/W interphase boundaries during the thermal degradation of Cu/W nano-multilayers is revealed. As rationalized on the basis of a modified Young equation, the large interface stress in the as-deposited NML decreases the thermodynamic driving force for the thermal grooving of W/W GBs. The experimentally derived interface stress linearly decreases with increasing annealing temperature. The onset of NML degradation, as initiated by grooving, only sets in after complete relaxation of the interface stress at around 650°C. The thus obtained fundamental knowledge may be exploited to tailor the thermal stability of immiscible NML systems and other types of immiscible nanomaterials by controlling the interface stress level during material synthesis. Graphical abstract: Image, graphical abstract